Legitimasi Kekuasaan dalam Perspektif Max Weber pada Pemerintahan Kontemporer - Qoirunnisa, Aninda; Yuyun Sri Wahyuni (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This article aims to analyze the legitimacy of power from Max Weber's perspective and review its application in contemporary governance. This research method uses a descriptive qualitative approach with a literature study approach. The researcher explores in-depth the concepts of power, authority, and legitimacy, as well as their relevance in modern governance practices. Data were collected through a review of books, journals, and academic articles, then analyzed using Weber's theoretical framework. The results show that the legitimacy of power depends not only on formal structures or legal rules, but also on social acceptance, public trust, and interactions between the government and society. Weber's typology of traditional, charismatic, and rational-legal authority remains relevant, but in the contemporary context, legitimacy is also influenced by transparency, public participation, and the use of information technology. These findings confirm that building and maintaining the legitimacy of power in contemporary governance requires a balance between formal legality, social recognition, and the effectiveness of public institutions.